2008
DOI: 10.1017/s1368980008002449
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption, eating behaviour and self-esteem among singlev. married and cohabiting mothers and their 12-year-old children

Abstract: Objective: Being a single mother may have implications for health behaviours that can also affect the child. More information about the food intakes and body weights in single v. married/cohabiting mothers and in their children is needed. Psychological dimensions of eating behaviour and self-esteem are also of relevance to explore for single mothers and their children. Design: Food style patterns were assessed by self-reported consumption of fruits, vegetables, sweets and soft drinks. Eating behaviour was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…showed restrictive patterns of eating more frequently than the girls from full families [35]. Considering social characteristics such as education or age of the mother, research results are rather consistent and show that these variables are significant for the child's nutritional status.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…showed restrictive patterns of eating more frequently than the girls from full families [35]. Considering social characteristics such as education or age of the mother, research results are rather consistent and show that these variables are significant for the child's nutritional status.…”
Section: Methodsmentioning
confidence: 61%
“…The results achieved by Camara et al [23] have shown that the mother's relationship status (single or with a partner) does not influence the way of feeding a child. In contrast, some research underlines the relationship between the health status and relationship status -being single relates to more unhealthy behavior [15,29,[35][36][37]. Research including pregnant women has shown that single mothers living with their parents consumed less fruit, vegetables and fiber and their diet contained more calories as compared to the reference group (married/with a partner).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have shown that poor self rated health was related to a low score on the prudent food intake pattern (prudent food was characterized by a frequent intake of whole meal bread, fruits and vegetables) (Osler et al 2001). Recent data demonstrated that marital status has been recognized as a significant health-influencing factor and being a single may have implications for health behaviours (Yannakoulia et al 2008; Elfhag and Rasmussen 2008). The findings of the other surveys on the association between marital status and dietary patterns are inconsistent: some investigators have shown that dietary patterns of married people are healthier (Fraser et al 2000; Riediger and Moghadasian 2008); other investigators have shown that dietary patterns were associated with marital status in men and women differently (Kriaucioniene et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research also indicates that being alone and lacking severe commitment from the part of Childs father effect the mother self esteem. 25,26 …”
Section: Discussionmentioning
confidence: 99%